Re-Emerging Vaccine-Preventable Diseases in War-Affected Peoples of the Eastern Mediterranean Region—An Update - Raslan, Rasha; El Sayegh, Skye; Chams, Sana; Chams, Nour; Leone, Angelo; Hajj Hussein, Inaya (Frontiers in Public Health, 2017)
For the past few decades, the Eastern Mediterranean Region has been one area of the world profoundly shaped by war and political instability. On-going conflict and destruction have left the region struggling with innumerable health concerns that have claimed the lives of many. Wars, and the chaos they leave behind, often provide the optimal conditions for the growth and re-emergence of communicable diseases. In this article, we will highlight three of the major re-emerging vaccine preventable diseases cholera, measles, and polio, in four countries of the Eastern Mediterranean Region that are currently affected by war leading to a migration crisis: Iraq, South Sudan, Syria, and Yemen. The review will outline the delicate interplay between war and the re-emergence and spread of these diseases in the context of failing healthcare systems. We will also describe the impact these infectious diseases have had on patients, societies and national health care services. The article will also describe the efforts, both local and international, that have been made to address these crises, as well as future endeavors that can be done to contain and control further devastation left by these diseases.